2007
DOI: 10.1088/0953-8984/19/4/046208
|View full text |Cite
|
Sign up to set email alerts
|

Electroresistive effects in electron doped manganite La0.7Ce0.3MnO3thin films

Abstract: The influence of electric current on the transport behaviour of La 0.7 Ce 0.3 MnO 3 thin epitaxial films on (001) LaAlO 3 substrate is studied. Measurements were carried out in the regime of low current densities (0.0325-32.5 A cm −2 ), for dc current in the absence of magnetic field. Significant reduction of the peak resistance (R p ) with monotonic increase in the metal-insulator transition temperature (T p ) was found with increasing bias current. The voltage current characteristics at various temperatures … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 36 publications
1
11
0
Order By: Relevance
“…This compound has been much studied and the resistance-temperature behaviour often reported [1,2,4,10,25,29,30,42,47]. The phase diagram predicts a MIT at ~250 K [30], and we observe T p = 245 K (Figs.…”
Section: = 03mentioning
confidence: 53%
See 2 more Smart Citations
“…This compound has been much studied and the resistance-temperature behaviour often reported [1,2,4,10,25,29,30,42,47]. The phase diagram predicts a MIT at ~250 K [30], and we observe T p = 245 K (Figs.…”
Section: = 03mentioning
confidence: 53%
“…The composition La 0.8 Ca 0.2 MnO 3 shows similar behaviour [33], with the mechanism again taken to be related to PS [18,34]. ER has also been observed in the related compounds La 0.7 Ce 0.3 MnO 3 [10], which is electron doped, La 0.67 Sr 0.33 MnO 3 [6,9,14] [7] and La 0.9 Sr 0.1 MnO 3 [22,33,36] it is observed that the ER and MR effects are decoupled. In ultrathin films [25] the non-linear characteristics are not intrinsic; extrinsic factors include contact resistance and joule heating.…”
mentioning
confidence: 59%
See 1 more Smart Citation
“…Interestingly -and indeed electroresistive effects in LCeMO were reported in the past [41] -the resistance of film D strongly depends on the measuring voltage. As visible in figure 2(b), in the whole temperature range investigated here, the resistance at 5 V is clearly lower than at 1 V. Furthermore, at 5 V, an MIT appears at 135 K. Being beyond the scope of the present work, the clarification of the origin of this electrical-field induced MIT (intrinsic to the film or substrate-related) by comparative magnetoresistance investigations is currently in progress [42].…”
Section: Resultsmentioning
confidence: 70%
“…Much of the previous work on ER has been reported for thin films and single crystals of manganites, e.g., LaO.7Cao.3Mn03, LaO.7Ceo.3Mn03 [32], LaO.67Sr0.33Mn03 [33,34], Ndo.6sCao.3sMn03 [35], Lao.gBao.1Mn03 [36], RO.67Ca0.33Mn03 [37], Cao.gCeo.1Mn03 [10], as well as the bi-layered manganite La1.2Sr1.8Mn207 [38J. ER in manganites is generally attributed to a percolative phase separation (PS) [39].…”
Section: Resultsmentioning
confidence: 99%